Surgical outcomes of middle fossa approach in intracanalicular vestibular schwannoma. (3rd April 2017) - Kang, Woo Seok; Kim, Shin Ae; Yang, Chan Joo; Nam, Sung Hoon; Chung, Jong Woo
Abstract: Conclusion: Middle fossa approach (MFA) shows a hearing preservation rate of 86% and facial nerve function was preserved with HB grade I or II in 93%. MFA is a good treatment option for intra-canalicular vestibular schwannomas when surgical excision is needed. Background: Surgical outcomes of vestibular schwannoma have progressively improved with the advancement of microsurgical instruments. MFA is known to have better chances to preserve hearing, while it has limited access to the posterior fossa, limitation of tumor size, and higher risk of post-operative facial nerve weakness. Objectives: To investigate surgical outcomes and clinical efficiency of MFA in vestibular schwannoma. Methods: A retrospective study was done in 14 patients who underwent MFA for vestibular schwannoma in Asan Medical Center. Results: The median age at diagnosis was 46.3 years. At initial presentation, 57% of the patients had vertigo, 43% hearing disturbance, and 64% tinnitus. The mean tumor size was 9.7 mm. The tumors were completely resected in 86% of the patients. Hearing was post-operatively preserved in 12 patients and two patients lost their hearing following surgery. Facial nerve function post-operatively remained unchanged in 12 patients (86%).